KONJUNGSI KOORDINATIF DALAM TALK SHOW MATA NAJWA - Nia Astriani; Hotma Simanjuntak; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractLanguage plays an critical part in human life. Humans use language in interrelated sentences. This connection can be seen in the first, second, and so on. In this manner, conjunctions is regularly utilized in communication. The research method used is descriptive with the form of qualitative research. The data source of this research in the Mata Najwa Talk Show episode of the reform exam section 1—7 and the data is the utterances (compound sentences equivalent to coordinate sentences) delivered by the speakers and presenters in the form of Mata Najwa Talk Show video as a data collection tool. The data analysis technique used in this study were transcription, reduction, classification, analysis, description, and conclusion. Based on the data analysis there were 394 data on the types of coordinate conjunctions (addition, selection, contradiction, correction, affirmation, limitation, sorting, equating, and inference) and 22 errors in the use of coordinate conjunctions. This study provides fantasy story texts and on implementation plan for learning Indonesian in the 2013 curriculum for grade VII semester 1.Keywords: Conjunction, Coordinate Conjunctions, Mata Najwa Talk Show